Lego Play Therapy for Managing Excessive Gadget Use in a School-Aged Child: A Pediatric Nursing Case Study - Shabrina Tsalis Nurfauziah; Andan Firmansyah; Dedi Supriadi; Sri Utami Asmarani (Yayasan Inspirasi El Burhani, 2026)
Background: Excessive gadget use among school-aged children has become an increasing concern because prolonged screen exposure may interfere with cognitive, emotional, and social development. Therapeutic play has been proposed as a non-pharmacological nursing intervention to encourage healthy developmental behaviors. Objective: To describe the implementation of Lego play therapy in managing excessive gadget use in a school-aged child through a pediatric nursing case study. Methods: A qualitative single-case study was conducted involving a 9-year-old girl who demonstrated excessive gadget use. Nursing assessment, observation, and parental interviews were performed before and after a three-day Lego play therapy intervention. Behavioral responses, social interaction, attention span, emotional regulation, and engagement in play activities were documented descriptively. Results: Following the intervention, the child demonstrated reduced interest in gadget use during therapy sessions, improved attention and concentration, increased verbal communication, better emotional regulation, and greater willingness to interact with family members. The intervention also encouraged creativity and active participation in constructive play. Conclusion: This case study suggests that Lego play therapy may serve as a practical nursing intervention to redirect excessive gadget use while promoting cognitive and social engagement in school-aged children. Further studies with larger samples, standardized outcome measures, and longer follow-up periods are required to confirm these preliminary findings